Hubungan Faktor Motivasi Dengan Kinerja Perawat dalam Pendokumentasian Discharge Planning di Rumah Sakit Siti Rahmah Padang: Relationship Between Motivation Factors and Nurse Performance in Documenting Discharge Planning at Siti Rahmah Hospital Padang - Dewi Murni; Esthika Ariany Maisa; Nicen Suherlin (NERS Jurnal Keperawatan, 2024)
Discharge planning is a series of decisions and activities in providing continuous and coordinated nursing care. Discharge planning must be known by the patient before the patient returns home. Discharge planning is related to nurse performance, if the nurse is good, the impact will be felt by the patient. Previous research stated that discharge planning was very influential on motivation. The purpose of this study was to determine the relationship between motivation with the documentation of Discharge Planning at RSI Siti Rahmah Padang 2018. A quantitative study with cross-sectional design was carried out in this study. The proportional stratified random sampling method has been used with 74 respondents as the sample. The data were collected using questionnaires containing documentation items discharge planning and motivation. The univariate analysis is presented by frequency distribution and bivariate tables using the chi-square test with 95% confidence degree (α=0.05). The results showed a significant relationship between motivation with the documentation of Discharge Planning at RSI Siti Rahmah Padang 2018 (p=0.000). It is recommended for nurses to maintain a good motivation.